A mode of error: Immunoglobulin binding protein (a subset of anti-citrullinated proteins) can cause false positive tuberculosis test results in rheumatoid arthritis. (December 2017) - Greenwald, Maria; Ball, JoAnn; Deodar, Atul
Abstract: Citrullinated Immunoglobulin Binding Protein (BiP) is a newly described autoimmune target in rheumatoid arthritis (RA), one of many cyclic citrullinated peptides(CCP or ACPA). BiP is over-expressed in RA patients causing T cell expansion and increased interferon levels during incubation for the QuantiFERON-Gold tuberculosis test (QFT-G TB). The QFT-G TB has never been validated where interferon is increased by underlying disease, as for example RA. Of ACPA-positive RA patients ( n  = 126), we found a 13% false-positive TB test rate by QFT-G TB. Despite subsequent biologic therapy for 3 years of all 126 RA patients, none showed evidence of TB without INH. Most of the false-positive RA patients after treatment with biologic therapy reverted to a negative QFT-G test. False TB tests correlated with ACPA level ( p  < 0.02). Three healthy women without arthritis or TB exposure had negative QFT-G TB. In vitro, all three tested positive every time for TB correlating to the dose of BiP or anti-BiP added, at 2 ug/ml, 5 ug/ml, 10 ug/ml, and 20 ug/ml. BiP naturally found in the majority of ACPA-positive RA patients can result in a false positive QFT-G TB. Subsequent undertreatment of RA, if biologic therapy is withheld, and overtreatment of presumed latent TB may harm patients.